El proceso de la gestión y el desempeño organizacional: una aproximación a la nueva gestión pública desde el ámbito de los gobiernos locales - Del Castillo, Carlos (2009)
The measurement of organizational performance, in particular the search for a model that brings the management process together with the expected results through strategies, has been one of the most important issues in the Administration in recent decades. Recently, efforts have been made to adapt to public sector organizations approaches and technologies originally developed for businesses, especially in countries such as Peru, seeking to influence governments’ ability to produce results. However, the concrete evidence of local government suggests that the implementation of management processes in this area reduces its chances of success because of the highly structured nature of management, the rigidity of the organizational design and the government regulation itself. This article argues that the performance improvement comes from reconciling the dimensions of the strategy and the structure. On this basis, there is a tool to assess organizational performance in terms of make flexible the functional structure and to adapt it towards logic of process management. In this way the strategy may gain intensity, causing the alignment of processes and create visible results of these, allowing to evaluate the performance of the areas, managers and ultimately, the organization.